Single arketamine in treatment resistant depression: Presentation of 3 cases with regard to sick-leave duration - Włodarczyk, Adam; Słupski, Jakub; Szarmach, Joanna; Cubała, Wiesław J. (Asian journal of psychiatry, 2024)
Ketamine is the prototypal rapid-acting antidepressant (RAAD) for TRD with approved indication for esketamine-nasal spray (ESK-NS). Distinctly, arketamine (R-KET) demonstrates enhanced antidepressant effects and neuroplasticity changes compared to esketamine, with fewer dissociative side effects and abuse potential. This study focuses on R-ketamine's therapeutic implications, safety, and tolerability in TRD treatment. We report on a year-long follow-up of three TRD patients post-single IV R-KET administration. The study, conducted under the clinical trial PCN-101 (NCT05414422), observed these subjects for healthcare resource utilization and social support system impact. Participants, adults diagnosed with recurrent major depressive disorder without psychotic features, were observed in a year-long follow-up period for safety. Case analyses revealed significant symptom reduction and improved social and vocational functioning, with reduced sick leaves and hospitalizations post-treatment. However, one case developed a substance use disorder, underscoring the need for vigilant monitoring. The study highlights R-KET's transformative potential in managing depression, indicating a shift in TRD treatment strategies towards early, aggressive interventions. Despite promising findings, the study faces limitations due to its small sample size, lack of randomization, and potential observational design biases. The results, while aligning with existing ketamine research, require cautious interpretation and warrant further investigation with larger, more robust studies. This exploration of R-KET's role in home-based TRD treatment opens avenues for future research, particularly focusing on its long-term effectiveness and safety in diverse patient populations. This study is registered in clinicaltrials.gov: NCT06232291.